The Influence of Education on Social Mobility in Rural Areas: Addressing Educational Inequalities for Sustainable Development - Hamdan Koswara (Journal of Education Innovation and Curriculum Development, 2024)
This research explores the influence of education on social mobility in rural areas, focusing on the barriers and opportunities that shape educational access and outcomes in these communities. The study examines how factors such as socio-economic status, infrastructure, gender, and government policies affect the potential for upward social mobility through education. Data was collected through surveys, interviews, and case studies across various rural regions, providing both qualitative and quantitative insights. The findings reveal that limited access to quality education, financial constraints, gender disparities, and socio-cultural norms significantly hinder educational attainment in rural areas, thereby restricting social mobility. Despite these challenges, the research highlights the positive impact of targeted policy interventions, such as scholarships and infrastructure development, in improving educational access. Furthermore, the study identifies the growing role of technology in bridging educational gaps, although technological barriers remain in many rural communities. The research concludes that addressing educational inequalities is crucial for promoting sustainable development and fostering social mobility in rural areas. It calls for comprehensive efforts to improve educational quality, infrastructure, and inclusivity, ensuring that education can be a transformative tool for socio-economic advancement in rural communities.